Making Mary Poppins : the Sherman Brothers, Walt Disney, and the creation of a classic film - Pierce, Todd James, 1965- (W. W. Norton & Company, 2025)
"Making Mary Poppins reveals the extraordinary true story behind the creation of one of the most beloved films of all time -- and the two little-known songwriters who helped make it possible. Long before Mary Poppins danced across the rooftops of Edwardian London and into the hearts of millions, Robert and Richard Sherman were struggling songwriters in Los Angeles, trying to find their voices -- and their futures. In this vivid and deeply researched narrative, author and Disney historian Todd James Pierce traces the unlikely path that brought the Sherman brothers to Walt Disney's attention, and how their personal history, musical genius, and emotional lives shaped the film's unforgettable songs and surprising storyline. From their early days writing novelty tunes to the high-stakes drama of working with P. L. Travers and Walt Disney himself, the Sherman brothers' story is rich with behind-the-scenes intrigue, creative breakthroughs, and quiet triumphs. Their work on Mary Poppins not only launched their careers -- it transformed Disney's live-action division and influenced an entire era of musical filmmaking. Filled with never-before-published details and backstage portraits, Making Mary Poppins is a story of art, ambition, and resilience. It's also a story of family -- of the bond between two brothers whose brilliance gave the world "Supercalifragilisticexpialidocious," "Feed the Birds," and a vision of magic that still resonates today." --